Nanocarriers-based therapeutic strategy for drug-resistant epilepsy: a systematic review - Díaz-Peregrino, Roberto; San Juan Orta, Daniel; Patiño-Ramirez, Carlos; Sandoval-Luna, Lenin V.; Arritola-Uriarte, Aleida (International journal of pharmaceutics, 2025)
Background - Nanocarriers have been proposed as a solution for drug-resistant epilepsy. - Methods - A systematic review of animal and in vitro studies was conducted to evaluate the efficacy, toxicity, and biological properties of nanocarriers. Searches were performed in PubMed/Medline and Scopus from March 2023 to March 2024. - Results - Eighteen studies were identified: 2 in vitro, 9 in vivo, and 7 combined. While epilepsy models and seizure control assessments were consistent, there was variability in evaluating the potential toxicity of nanocarriers. Only one study did not show a reduction in brain inflammation, seizures, and cell loss. Nanocarrier toxicity was evaluated just in six studies, all of which indicated low toxicity both in vitro and in vivo. - Conclusions - Nanocarriers with antiseizure drugs manage seizures, inflammation, oxidative stress, and behavior impairment in drug-resistant epilepsy. Furthermore, nanocarriers are a safe option for delivering antiseizure drugs, though more research is needed to confirm these findings.